Use of epidemiological principles in research and scientific publications - future perspective - Wagle, RR (Nepalese Journal of Ophthalmology, 2011)
DOI: 10.3126/nepjoph.v3i1.4296 Nepal J Ophthalmol 2011;3(5):94